Peran pengawasan, pembuatan kebijakan, dan penetapan proses risiko dalam manajemen risiko - Eltari, Miskah Fitriani (Maliki Interdisciplinary Journal, 2024)
Islamic bank’s principles, different from conventional banks, face unique challenges in managing liquidity risk. Liquidity risk occurs when a bank fails to meet its financial obligations to customers in a timely manner, influenced by internal and external factors such as financial market sensitivity and economic shocks. Effective liquidity management is crucial for Islamic banks to maintain a balance between liquidity supply and demand, avoid significant losses, and uphold good relationships with regulators. Islamic banks need to adopt liquidity instruments in line with Sharia principles and develop contingency plans to address such risks. The implementation of liquidity risk management involves stringent oversight from the board of directors, commissioners, and Sharia Supervisory Board, the formulation of systematic policies, procedures, and risk limits, as well as the establishment of accurate risk processes and management information systems. Consequently, Islamic banks can mitigate liquidity risk, maintain stability, and support inclusive and sustainable economic development.